Generalizeo - diffusive theory of solid mixtures. II. Thermo - elastic compozite - Chanh, Trương Minh (Vietnam Journal of Mechanics, 1982)
A theory of thermo-elastic compozite materials is proposed. It is based on the generalized- diffusive theory of mixture. The influence of viscous dissipation is included in the general treatment. The linear version of the constitutive equations in the absence of the viscosity is exhibited in, detail in the case of isotropic compozite.